Program Implementation Analysis Of School Health Unit Program In SD Negeri 3 Kepanjen - Silvia, Eka; Sari, Nia; Arina Chusnatayaini (Universitas STRADA Indonesia, 2019)
School-aged children are a critical age group because at that age a child is vulnerable to health problems. In addition to being susceptible to health problems, school age children are also at a very sensitive condition to the stimulus. The general purpose of this research is to analyze the implementation of School Health Program in SD Negeri 3 Kepanjen The design of this research was quantitative with cross sectional approach. The population of this research was all students in SD Negeri 3 Kepanjen Malang Regency. The sample size was 103 respondents taken by Simple Random Sampling technique. Variable dependent implementation of School Health Unit, independent variable knowledge, attitude, facilities and infrastructure, and teachers and health workers. The result of analysis using logistic regression. The result of the research shows that there is a correlation between knowledge with the implementation of UKS with value 0.000, there is relationship between attitude with UKS implementation with value 0,000, there is relationship between means of infrastructure with UKS implementation with value 0,026, there is relation between teacher and health worker with UKS implementation with ρ value 0.000, The more influential factor with the implementation of UKS with value of ρ value 0,000 is the knowledge variable. In order for the implementation of School Health Unit to run properly and actively, it requires the knowledge and attitude of the students and the supporting facilities that can be used to implement the School Health Unit program. The existence of guidance from teachers and health workers is also very necessary to support the implementation of School Health Unit.